Efeito do intervalo para início da radioterapia em pacientes com glioblastoma - Loureiro, Luiz Victor Maia [UNIFESP] (2017)
Objective: to evaluate the effect of waiting time between the neurosurgical intervention and the starting of radiotherapy on overall survival of Glioblastoma patients as an independent prognostic variable. Methods: two different methods were applied: 1) cohort study; 2) systematic review and meta-analysis. Cohort of 115 Glioblastoma patients from two different health-care institutions (one public and one private) who underwent post-operative radiotherapy. A systematic review of studies published between 1975 and 2015 reporting on the waiting time to radiotherapy for Glioblastoma patients who underwent a neurosurgical procedure. The meta-analysis was performed by converting the waiting time to radiotherapy studies intervals into a regression coefficient (β) and standard error expressing the effect size on overall survival per week of delay. Results: for the entire cohort the median waiting time to radiotherapy was 6 weeks (range, 1.3 – 17.6). The median overall survival for waiting time < 6 weeks was 13.5 months (95% CI, 9.1 – 17.9) and for those > 6 weeks was 14.2 months (95% CI, 11.2 – 17.2) (HR 1.16, 95% CI 0.77 – 1.76; p = 0.47). The waiting time to radiotherapy had no significant effect on overall survival even when compared to well- known prognostic variables (HR 1.32, 95% CI, 0.73 – 2.39; p = 0.35). Data required to calculate the effect size on overall survival were available for 14 studies retrieved for systematic review, including 5,429 patients. The combined analysis showed a median waiting time to radiotherapy of 37 days (ranges, 1 – 232) and provided no evidence for an association between waiting time to radiotherapy, per week of delay, and overall survival (HR 0.98, 95% CI, 0.89 – 1.07; p = 0.61). Conclusions: the waiting time to radiotherapy was not an independent prognostic variable for overall survival of Glioblastoma patients and had no significant effect on overall survival even when compared to well-known prognostic variables. The meta-analysis provided no evidence of a true effect on overall survival by delaying radiotherapy.